Grading carcinoembryonic antigen levels can enhance the effectiveness of prognostic stratification in patients with colorectal cancer: a single-centre retrospective study - Hailun Xie; Lishuang Wei; Qiwen Wang; Shuangyi Tang; Jialiang Gan (BMJ Open)
Objectives This study developed a refined carcinoembryonic antigen (CEA) grading system using CEA cut-off points of 5, 20 and 50 ng/mL and to explore the prognostic value of CEA grading in predicting the progression-free survival (PFS) and overall survival (OS) of colorectal cancer (CRC) patients.Design A retrospective cohort study.Setting First Affiliated Hospital of Guangxi Medical University.Participants 1107 CRC patients who received surgical treatment.Materials and methods Survival analysis was conducted using the Kaplan-Meier method and compared using the log-rank test. A Cox regression model with a 95% CI was used to evaluate the independent prognostic risk factors for CRC. Prognostic nomograms were constructed to predict the 1–5-year PFS/OS.Results Elevated serum CEA levels are often indicative of recurrence and death in CRC patients. Higher CEA levels were significantly associated with more aggressive tumour phenotypes. The CEA grading system was an independent predictor of prognosis in CRC patients and effectively stratified PFS (62.0% vs 51.2% vs 33.7% vs 20.2%, p<0.001) and OS (64.7% vs 54.4% vs 36.6% vs 22.5%, p<0.001) in CRC patients. As the CEA grade increased, the risk of poor prognosis gradually increased in a gradient manner, with an approximately 10% difference in risk grade between each CEA grade. The internal validation cohort further confirmed that CEA grade remains an effective prognostic factor for the survival of CRC patients. Prognostic nomograms, which integrate individual characteristics, tumour features and CEA grading, provide a more comprehensive prognostic evaluation for CRC patients.Conclusions The CEA grading system is an independent predictor of prognosis for CRC patients and can effectively stratify PFS and OS.